Seminar Digitalisasi Industri UMKM dan Efisiensi Listrik Untuk Kemajuan Ekonomi Desa - Fajar Gumilang; Ilham Pratama; Imron Rosidi N.H; Puji Rahayu; Sri Lestari (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The development of digital technology and the need for energy efficiency are two important elements in advancing the village economy, especially through the Micro, Small and Medium Enterprises (MSME) sector. The digitalization of MSMEs opens up great opportunities for village business actors to expand markets, increase productivity and integrate technological innovation in their operations. Meanwhile, electricity efficiency not only has an impact on reducing production costs, but also contributes to environmental sustainability. This research aims to analyze the impact of digitalization and electricity efficiency on village economic progress through the development of MSMEs. This study examines how digitalization can increase market access and competitiveness of MSMEs in villages, as well as how implementing energy efficiency practices can reduce the burden of operational costs faced by business actors. Apart from that, this research also discusses the challenges faced by MSMEs in villages in adopting digital technology and energy efficiency practices, as well as solutions that can be implemented to overcome these challenges. The research results show that the integration of digitalization and electricity efficiency can make a significant contribution to improving the performance of MSMEs in the village, which in turn has a positive impact on improving the overall village economy. Successful implementation requires strong support from governments, technology providers and local communities to ensure the sustainability of these initiatives